2012
DOI: 10.1111/j.1365-2958.2012.08205.x
|View full text |Cite
|
Sign up to set email alerts
|

The biofilm formation defect of a Bacillus subtilis flotillin‐defective mutant involves the protease FtsH

Abstract: Summary Biofilm formation in Bacillus subtilis requires the differentiation of a subpopulation of cells responsible for the production of the extracellular matrix that structures the biofilm. Differentiation of matrix-producing cells depends, among other factors, on the FloT and YqfA proteins. These proteins are present exclusively in functional membrane microdomains of B. subtilis and are homologous to the eukaryotic lipid raft-specific flotillin proteins. In the absence of FloT and YqfA, diverse proteins nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
107
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(116 citation statements)
references
References 79 publications
(141 reference statements)
7
107
2
Order By: Relevance
“…2c). Contrary to the previous report (Yepes et al, 2012), we also observed that the floTA mutant strains showed similar sporulation efficiencies to those of the WT strain in liquid MSgg medium (Table S4), indicating that the flotillin proteins are not involved in sporulation in the undomesticated strain. Taking all these results together, we conclude that KinC activity required for biofilm formation is independent of the bacterial flotillin-like proteins FloT and FloA under the conditions tested.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…2c). Contrary to the previous report (Yepes et al, 2012), we also observed that the floTA mutant strains showed similar sporulation efficiencies to those of the WT strain in liquid MSgg medium (Table S4), indicating that the flotillin proteins are not involved in sporulation in the undomesticated strain. Taking all these results together, we conclude that KinC activity required for biofilm formation is independent of the bacterial flotillin-like proteins FloT and FloA under the conditions tested.…”
Section: Resultscontrasting
confidence: 56%
“…1a). We also found that sporulation efficiency in the floTA mutants is similar to the levels observed in the WT strains under starvation conditions [~10 8 spores (ml culture) 21 ] in DSM, contrary to the results reported by Yepes et al (2012) on MSgg medium.…”
Section: Resultscontrasting
confidence: 55%
“…First, it is attributed to us that the floTA mutant phenocopies the kinC mutant, but we have actually published that they have different sporulation efficiencies (Yepes et al, 2012). In addition, it is attributed to us that the flotillin-deficient mutant shows reduced sporulation, but this observation was initially reported by another laboratory (Donovan & Bramkamp, 2009) and later confirmed by us (Yepes et al, 2012). Finally, the localization of KinC in a single membrane focus was also attributed to us.…”
Section: Connection Of Kinc To Flotillins and Potassium Leakage In Bamentioning
confidence: 72%
“…These membrane regions contain two scaffold proteins named flotillins (FloT and FloA) that may facilitate interaction of functional membrane microdomainassociated proteins. Consequently, a flotillin-deficient strain shows reduced activity of KinC and other functional membrane microdomain-associated proteins, which leads to a decreased capacity to form a biofilm via activation of KinC Yepes et al, 2012). A recent publication from the laboratory of Professor Masaya Fujita (University of Houston, Houston, TX, USA) (Devi et al, 2015) shows that the tetrameric form of KinC is required to activate biofilm formation.…”
Section: Connection Of Kinc To Flotillins and Potassium Leakage In Bamentioning
confidence: 99%
“…Also, the protease FtsH, which is involved in control of Spo0A, the master regulatory protein controlling biofilm formation and sporulation, is organized in lipid rafts [Yepes et al, 2012]. It would be of interest to look for rafts in other types of bacteria and to elucidate their lipid composition.…”
Section: Lipid Raftsmentioning
confidence: 99%